Research of Neural Network Learning Rate Control Methods for the Automatic Signal Type Recognition - Grigoryan, T. A.
A neural network with dynamic parameters and algorithms for the learning rate hyperparameter control has been developed in the LabVIEW software environment in order to increase the efficiency of the signal type recognition algorithm and reduce the network training time. The learning rate hyperparameter control methods testing results are presented. As a result, the most effective method for this task was selected.
Keywords: Physics